Any number that you choose can be the next number. It is easy to find a rule based on a polynomial of order 4 such that the first four numbers are as listed in the question followed by the chosen next number. There are also non-polynomial solutions. Short of reading the mind of the person who posed the question, there is no way of determining which of the infinitely many solutions is the "correct" one.
The simplest solution, based on a binomial is
U(n) = 21 - 15n for n = 1, 2, 3, ...
and accordingly, U(10) = -129.
If you mean: 34 39 24 ... then the nth term is 39-5n and so the 100th term = -461
To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by 9, then 13, then 17, and so on. This pattern indicates that the nth term is given by the formula n^2 + n - 1. So, the nth term of the sequence 0, 9, 22, 39, 60 is n^2 + n - 1.
Continuing the sequence would be the the numbers 24, 31, 39.
39% of 62 = 62*39/100 = 24.18 = 24.2 to the nearest tenth
63, 102, 165...
If you mean: 34 39 24 ... then the nth term is 39-5n and so the 100th term = -461
24 - 27 - 30 - 33 - 36 - 39 - 42 etc. * 27 is 3 larger than 24 * 30 is 3 larger than 27 * ... and so on
39
To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by 9, then 13, then 17, and so on. This pattern indicates that the nth term is given by the formula n^2 + n - 1. So, the nth term of the sequence 0, 9, 22, 39, 60 is n^2 + n - 1.
Continuing the sequence would be the the numbers 24, 31, 39.
39% of 62 = 62*39/100 = 24.18 = 24.2 to the nearest tenth
63, 102, 165...
A single term, such as 51474339 does not define a sequence.
One tenth of 390 is equal to 39. To find one tenth of a number, you divide the number by 10. In this case, 390 divided by 10 equals 39. Therefore, one tenth of 390 is 39.
39. The rule here is starting with the number 9, add (-6 + sequence number * 6). 9 + (-6) = 3 3 + 0 = 3 3 + 6 = 9 9 + 12 = 21 21 + 18 = 39 39 + 24 = 63
I'm going to assume by "most probable answer" you mean the next term? The next term is 63. The pattern in this sequence is to add the preceding number to the current number to get the next number. For example, to get to 9, you add 3 to 6. To get to 15, you add 6 to 9 and so on and so forth.
x + 17 = 14, x =